QUO VADIS THE INSTITUTIONAL TRANSFORMATION OF INDONESIAN TAXATION? (PERCEPTION OF THE ACADEMICIANS, TAX CONSULTANTS , AND TAXPAYERS IN MALANG CITY) - Sugiarto, Robby (Jurnal Ilmiah Mahasiswa FEB, 2017)
The tax agency in Indonesia has not performed very well as shown by its inability to achieve the tax revenue targets in the last few years. Such a condition is responded by the government by planning the institutional transformation of Indonesian taxation as a result of performance evaluation listed in the Draft of Tax Law â€œRUU KUPâ€ 2016. This descriptive qualitative research aims to observe the problems faced by DJP, identify the perception of academicians, tax consultants, and taxpayers on the transformation of the tax agency in Indonesia. and examine the perception on the concept of institutional forms of tax agencies after the transformation. Â The data are collected through document study and interview towards the research informantsÂ  determined Â by Â purposive sampling Â method Â combined Â with Â snowball sampling technique. The result of the study reveals three major problems encountered by DJP, i.e. that the tax ratio and tax compliance are low, the tax revenue target has not been achieved, and the authority of the tax agency in Indonesia is limited. The institutional transformation plan gains positive response from the informants because the policy gives wider autonomy and independence to the taxation institutions. As the transformation is implemented, the tax agency in Indonesia shall consider semi- autonomous concept as the appropriate choice within the current conditions with regard to the plans stated in the Article of Tax Law â€œRUU KUPâ€ 2016.Keywords: Institutional transformation; Autonomy